Pengaruh Aplikasi Teknologi, Accounting Reporting Terhadap Pencegahan Fraud Serta Implikasinya Terhadap Reaksi Investor - Yulita Zanaria (Universitas Muhammadiyah Metro, 2017)
The purpose of this research is to examine the impact of information technology, accounting reporting toward fraud detection in companies that listed on Indonesia Stock Exchange. Baside that, this research to examine implication of fraund detection to investor reaction. The population of the study is the LQ 45 companis registered in the Indonesia Stock Exchange in the periode of 2010-2014. Shampling technique employed in this study is the purposive sampling whit the total sample of 90 companies The data analysis uses Amos software, The result of the study show yhat the dividend policy, information technology, accounting reporting have significant influence towards frund detection. The other result showed that fraund detection have significant influence towards investor reaction. Keywords :information technology, accounting reporting, fraund detection, investor reaction.